2015
DOI: 10.1039/c5sm01229e
|View full text |Cite
|
Sign up to set email alerts
|

Are polymers glassier upon confinement?

Abstract: Glass forming systems are characterized by a stability against crystallization upon heating and by the easiness with which their liquid phase can be transformed into a solid lacking of long-range order upon cooling (glass forming ability). Here, we report the thickness dependence of the thermal phase transition temperatures of poly(l-lactide acid) thin films supported onto solid substrates. The determination of the glass transition, cold crystallization and melting temperatures down to a thickness of 6 nm, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 59 publications
2
22
1
Order By: Relevance
“…Slow-cooled PHF and PBF thin films, showed the development of clearly defined polymer crystals (Figure 1 g) and i)). In particular, PHF developed large structures, typically observed for polymer spherulites [36,58], while PBF showed smaller needle-like crystals. The formation of these nanostructures was also accompanied by an important change in the surfaces' roughness.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Slow-cooled PHF and PBF thin films, showed the development of clearly defined polymer crystals (Figure 1 g) and i)). In particular, PHF developed large structures, typically observed for polymer spherulites [36,58], while PBF showed smaller needle-like crystals. The formation of these nanostructures was also accompanied by an important change in the surfaces' roughness.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, polymer thin films have been a subject of academic debates for over the past 20 years [28][29][30][31]. In the particular case of semicrystalline polymers, the confinement imposed by the thin film geometry, and the polymer-substrate adsorption effects, resulted in differences in the crystallization rate [32,33], crystalline morphology [34][35][36], thermal transitions and polymers' molecular dynamics [32,37]. In turn, preparing poly(alkylene 2,5-furanoate)s can be also a way to tune their physical properties, at nanoscale levels.…”
Section: Introductionmentioning
confidence: 99%
“…The physical nature of the deviations has been attracting much attention in the past two decades. 1,2 Model systems have been constructed and investigated extensively, in particular polymer thin films, 3,4 and nanocomposites. [5][6][7] Generally, depending on the choice of polymer and substrate, changes of segmental relaxation time or shifts in the glass transition temperatures (both increases or decreases with confinement) have been reported, which is usually discussed as a counterbalance of different factors.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the critical interfacial interaction and the film thickness further demonstrates the presence of a finite size effect and the entropic barrier effect from another point of view. Figure (b) shows the crystallinity for films of two different thicknesses with the same interfacial interaction during the cooling and heating processes.…”
Section: Resultsmentioning
confidence: 81%
“…In experiments, Spièce et al found that the finite size of crystals in the films can also affect the melting point. 43 In films with higher interfacial interaction, crystal lamella thickening is restricted, leading to relatively thinner lamellae and lower melting points. In other words, the finite size effect offsets the density effect, and thus the melting points do not depend on the interfacial interactions.…”
Section: Resultsmentioning
confidence: 99%